Oxidative Stress and Total Antioxidant Capacity in Rheumatoid Arthritis. - Mahmood, Halla G.; Ali, Zeyan A.; Abdulhameed, Raed A.; Hussein, Ilham M. (Journal of the Faculty of Medicine Baghdad, 2014)
Back ground:-Rheumatoid arthritis (RA) is a systemic disease characterized by progressive, erosive and chronic poly arthritis, where cellular proliferation of the synoviocytes and neo-angiogenesis leads to formation of pannus which destroys the articular cartilage and the bone . Objective :-to evaluate theOxidative Stress index( OSI )by measuring malondialdehide( MDA) and Total Antioxidant Capacity( TAC) in serum of RA patients in addition to uric acid and albumin and to investigate the alteration in these parameters compared to healthy individuals. Patients and Methods :- twenty five patients with rheumatoid arithritis and twenty five apparently healthy subjects matched for age and weight have been included in this study,uricacid and Serum malondialdehyde were measured by enzymatic methods. serum total antioxidant capacity was measured according to Miller et al method. Results :-The data obtained showed that the serum levels of Albumin, the total antioxidant capacity were significantly lower in patients with RA than in healthy controls.While the serum levels of MDA,uric acid were significantly higher in patients with RA than in healthy controls. Conclusion:- there is acontribution of antioxidant to the pathogenesis of RA.